2021
DOI: 10.1093/jhps/hnab023
|View full text |Cite
|
Sign up to set email alerts
|

What is the pelvic tilt in acetabular dysplasia and does it change following peri-acetabular osteotomy?

Abstract: To quantify the pelvic tilt (PT) in patients with symptomatic acetabular dysplasia and determine if it represents a compensatory mechanism to improve femoral head coverage, we studied a cohort of 16 patients undergoing 32 bilateral staged PAOs for acetabular dysplasia and compared this to a matched cohort of 32 patients undergoing PAO for unilateral acetabular dysplasia all with >1 year follow-up. The change in PT was determined with two validated methods, namely, the sacro-femoral-pubic (SFP) angle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
(51 reference statements)
3
17
1
Order By: Relevance
“…However, it is likely that one’s pelvic tilt angle cannot be altered much, as previous studies have reported that functional pelvic tilt angle does not change after successful PAO in both retroversion and dysplasia cases (ie, absent compensatory mechanisms). 16 , 37 We would thus argue that it is the functional version that has to be accounted for and treated, and that one’s spinopelvic parameters play an important role as primary determinants of the functional version.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that one’s pelvic tilt angle cannot be altered much, as previous studies have reported that functional pelvic tilt angle does not change after successful PAO in both retroversion and dysplasia cases (ie, absent compensatory mechanisms). 16 , 37 We would thus argue that it is the functional version that has to be accounted for and treated, and that one’s spinopelvic parameters play an important role as primary determinants of the functional version.…”
Section: Discussionmentioning
confidence: 99%
“…PT was measured by the sacro-femoral-pubic (SFP) angle, and the pubic symphysis to sacroiliac (PS-SI) index, in both supine and standing AP pelvic radiographs for all 69 patients. The preoperative radiographs were also assessed for acetabular index (AI) 26 and lateral centre-edge angle (LCEA). 26 A review of the patients’ notes found that, of the 22 patients with preoperative supine and standing radiographs, 28 hips were symptomatic for acetabular retroversion.…”
Section: Methodsmentioning
confidence: 99%
“…The preoperative radiographs were also assessed for acetabular index (AI) 26 and lateral centre-edge angle (LCEA). 26 A review of the patients’ notes found that, of the 22 patients with preoperative supine and standing radiographs, 28 hips were symptomatic for acetabular retroversion. These 28 symptomatic hips were then assessed for the parameters of acetabular retroversion: crossover sign, crossover index, ischial spine sign, and posterior wall sign.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations